2016
DOI: 10.2147/jpr.s55571
|View full text |Cite
|
Sign up to set email alerts
|

The role of the arginine metabolome in pain: implications for sickle cell disease

Abstract: Sickle cell disease (SCD) is the most common hemoglobinopathy in the US, affecting approximately 100,000 individuals in the US and millions worldwide. Pain is the hallmark of SCD, and a subset of patients experience pain virtually all of the time. Of interest, the arginine metabolome is associated with several pain mechanisms highlighted in this review. Since SCD is an arginine deficiency syndrome, the contribution of the arginine metabolome to acute and chronic pain in SCD is a topic in need of further attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…Arginine supplementation along with hydroxyurea increases level of HbF and nitrite [ 29 ]. Preliminarily outcome of phase 2 clinical trial showed that reduced arginine induces pain and vaso-occlusive crisis (VOC) which is alleviated through arginine supplementation in SCD patients [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Arginine supplementation along with hydroxyurea increases level of HbF and nitrite [ 29 ]. Preliminarily outcome of phase 2 clinical trial showed that reduced arginine induces pain and vaso-occlusive crisis (VOC) which is alleviated through arginine supplementation in SCD patients [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“… 33 , 36 NO-dependent blood flow is impaired in SCD patients. 27 , 40 , 41 Several studies have indicated the improvement of SCD and associated complications using arginine therapy, 42 – 44 due to the failure of NO-based therapeutic effect. 45 , 46 Thus, arginine supplementation may be required in the SCD patients with complications studied, especially those with VOC.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine (found here to decrease in the plasma) is related to both pain and NO metabolism and has been shown to mitigate pain in a phase III clinical trial in sickle cell disease [24]. Arginine metabolism also plays a key role in pain in sickle cell disease [10]. In effect, arginine supplementation has been shown to reduce pain via increased blood NO levels in a double-blind clinical trial [25].…”
Section: Metabolites Potentially Associated With Painmentioning
confidence: 99%
“…It is worth noting that DMA and most of these amino acids are linked to arginine and nitric oxide (NO) metabolism. In effect, the steady state of the disease is known to be associated with a decrease in arginine concentration because of arginine consumption to synthesize ornithine, polyamines, proline, and glutamate (via arginase) rather than NO (via NO synthase) [9,10]. During hemolysis, arginase is liberated from red blood cells and competes with NO synthases for arginine consumption and, furthermore, free hemoglobin fixes NO.…”
Section: Plasmatic Metabolic Signaturementioning
confidence: 99%